Chemical analysis and biological properties of two different formulations of white portland cements - Aly Ahmed, Hany Mohammed; Luddin, Norhayati; Kannan, Thirumulu Ponnuraj; Mokhtar@Makhtar, Khairani Idah; Ahmad, Azlina (John Wiley and Sons Inc., 2016)
White Portland cement (WPC) has generated research interests in the field of endodontics. This study compared between the properties of two formulations of white Portland cement (WPC) of different origin (Malaysia [MA] and Egypt [EG]). WPCs with and without calcium chloride dihydrate were prepared. Scanning electron microscope (SEM), energy dispersive X-ray micro-analysis, and X-ray diffraction were used for surface morphology evaluation, elemental, and phase analysis, respectively. After the preparation of optimized serial dilutions, the cytotoxicity was evaluated on human periodontal ligament fibroblasts (HPLFs) and dental pulp stem cells (DPSCs) using methyl-thiazol-diphenyltetrazolium assay after 24 and 72 h. Cell attachment properties were examined under SEM after 24 and 72 h. Results showed that the surface morphology and chemical composition of both formulations demonstrated detectable variations. The cytotoxicity evaluation showed different cellular responses of HPLFs compared to DSPCs. Both formulations favored the viability of HPLFs. However, the fast set formulations demonstrated severe cytotoxicity on DPSCs. Significant differences between EGWPC and MAWPC were identified (p < 0.05). The cell attachment properties were favorable; however, HPLFs attached and spread over the samples better than DPSCs. In conclusion, WPC of different origin may show differences in chemical and biological properties. The addition of CaCl2 ·2H2 O to WPC can affect its properties. Human cell types may react differently towards different formulations of WPCs. SCANNING 9999:1-14, 2015. © 2015 Wiley Periodicals, Inc.